تأثير الاحتباس الحراري على الأمراض الفيروسية المنقولة عن طريق البعوض - شويرفات, يسرى; غراب, مسعودة; يحي, زينب (University of Eloued جامعة الوادي, 2023)
Greenhouse gas emission caused by human activity will lead to climate change, which will mostly affect human health negatively. More than 80% of the world's population is at risk of contracting diseases transmitted by mosquitoes; These diseases are the largest contributors to the burden of diseases transmitted to humans. Research to date has focused strongly on the role of climate change. It has been observed that global economic development, precipitation and temperature are responsible for the increase in the pattern and dynamics of transmission of mosquito-borne diseases. However, mosquito control is essential to prevent mitigate human-to- human transmission of yellow fever, dengue and other viruses in a changing world.
تنوع حيوي ومحيط
Keywords: climate; diseases; mosquitoes; yellow fever; dengue fever.; المناخ، الأمراض، البعوض، الحمى الصفراء، حمى الضن